2014
DOI: 10.3732/ajb.1300223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the purple‐flowered ancestor of garden petunias

Abstract: Our work will contribute to the clarification of the evolutionary relationships among the Petunia ×hybrida and P. integrifolia taxa group and could be useful in breeding programs to transfer desired traits from wild to cultivated species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
0
21
1
Order By: Relevance
“…2011 ). A recent study involving wild Petunia species and commercial P. hybrida ( Segatto et al . 2014 b ) showed that P. integrifolia species complex share several alleles and also have a low mean number of alleles per locus (five in Petunia inflata , four in P. integrifolia and three in Petunia interior ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011 ). A recent study involving wild Petunia species and commercial P. hybrida ( Segatto et al . 2014 b ) showed that P. integrifolia species complex share several alleles and also have a low mean number of alleles per locus (five in Petunia inflata , four in P. integrifolia and three in Petunia interior ).…”
Section: Discussionmentioning
confidence: 99%
“…2010 ; Fregonezi et al . 2013 ), and one artificial hybrid known worldwide, the commercial Petunia hybrida that is the result of crossings between Petunia axillaris and Petunia interior ( Segatto et al . 2014 b ).…”
Section: Introductionmentioning
confidence: 99%
“…The commercial P. hybrida is derived from crosses between a white-flowered, moth-pollinated P. axillaris, and species of the P. integrifolia clade, a group of closely related bee-pollinated species and subspecies ( Fig. 1) 6,7 .…”
mentioning
confidence: 99%
“…The garden petunia, Petunia hybrida, was bred from mothpollinated P. axillaris and a bee-pollinated species of the P. integrifolia clade that includes P. inflate (Segatto et al, 2014;Stehmann et al, 2009), producing a wide variety of cultivars. The white-flowered P. axillaris has a strong and sweet fragrance during the night.…”
Section: Introductionmentioning
confidence: 99%